First person - Zakia Abdelhamed (The Company of Biologists, 2020)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Zakia Abdelhamed is first author on 'A novel hypomorphic allele of Spag17 causes primary ciliary dyskinesia phenotypes in mice', published in DMM. Zakia is a research associate in the lab of Dr Rolf Stottmann at Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USA, investigating animal models that recapitulate a human condition for understanding disease pathogenesis.